PERAN SATUAN PENGAMANAN DALAM UPAYA PENCEGAHAN KERIBUTAN ANTAR WARGA BINAAN DI LAPAS SIBORONGBORONG KELAS II B - Sibarani, Irvan; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
As an important component of the criminal justice system, correctional institutions serve as mentorship programs for inmates and students enrolled in them. Human resources are the main consideration in choosing security measures in correctional institutions. Therefore, officers in prison security units play an important role in enforcing prison security. The main task of the prison security unit is to maximize and minimize errors to ensure that there are no disturbances or security violations in the prison. It is generally acknowledged that prison overcrowding is a problem. There is an inverse relationship between the increasing volume of crime in Indonesia and the capacity of correctional institutions and detention centers, which in this case are places for providing services and guidance. This type of research is empirical legal research (empirical juridical) using a statutory approach method, and empirical juridical or facts that occur in practice in the field. The data collection techniques used in this research are library research and field study techniques. Data collection tools can be in the form of observations and interviews. The results of the research show that the role of prison security units in preventing commotion between inmates is very important and effective when carried out in the right way, such as routine supervision, quick and effective response to an incident and the importance of education for inmates and collaboration with other parties is the key to success in creating a safe, comfortable and orderly prison environment.